CYBERSECURITY LAW OF MONGOLIA: DEFINITION, IMPLEMENTATION, AND ITS IMPACT ON NATIONAL SECURITY - Munkhjargal Bayanjargal,; Munkhtsetseg Erdenebulgan,; Byambadorj Dondogmegd,; Odmaa Luvsan, (International Journal of Innovative Technologies in Social Science, 2025)
The Cyber Security Law enacted in Mongolia in 2022 is the initial comprehensive legal framework aimed at safeguarding the cyber environment, yet there are uncertainties and deficiencies in its enforcement.This study seeks to examine the terminology, risk assessment, and regulatory methodology for information security audits under the Mongolian Cyber Security Law, assess their impact on national security, and compare and evaluate them against international practices.The analysis involved a review of relevant Mongolian laws, regulations from the Ministry of Electronic Development, and information from authorized entities, along with a quantitative and qualitative comparison of the implementation levels of information security audits and cybersecurity risk assessments.Additionally, comparisons were made with international standards such as ISO/IEC 27001, ISO/IEC 27005, NIST SP 800-30, ENISA, and the cybersecurity practices of countries like Estonia, Singapore, and South Korea. While Mongolia has a foundational legal framework for cybersecurity, significant shortcomings persist in its execution. To address these issues, it is imperative to refine terminology, establish a national audit body, standardize risk assessment and audit methodologies in alignment with global standards, establish a centralized monitoring and inspection system, develop a national centralized platform, and enhance human resource capabilities. These measures are crucial for safeguarding national security and ensuring the resilience of Mongolia’s cyber environment.